Natalizumab treatment is associated with peripheral sequestration of proinflammatory T cells - Kivisäkk, P (American Academy of Neurology, 2009)
BACKGROUND: Natalizumab is an antibody directed against integrin α4 that reduces disease activity in patients with multiple sclerosis (MS) by blocking migration of T and B cells into the CNS. The goal of this study was to characterize the effects of natalizumab treatment on cytokine production and expression of activation markers, costimulatory molecules, and trafficking determinants on CD4(+) and CD8(+) T cells. METHODS: In a longitudinal study, we investigated the expression of surface makers and cytokine expression on peripheral blood lymphocytes from 28 patients with MS who started natalizumab treatment and were followed for 1 year. A mixed effects model was used to compare pretreatment to on-treatment measurements. RESULTS: The frequency of CD4(+) T cells producing interferon-γ, tumor necrosis factor, and interleukin (IL)-17 upon anti-CD3 stimulation increased 6 months after initiation of natalizumab treatment and remained elevated throughout the follow-up. The frequency of CD4(+) T cells expressing CD25, HLA-DR, and CCR6 ex vivo was increased at one or more time points during treatment. Among CD8(+) T cells, the frequency of cells producing IL-2 and IL-17 after stimulation was increased during natalizumab treatment, as was the frequency of CD8(+) T cells expressing CD58 and CCR5 ex vivo. The increase in the frequency of activated cells could not be replicated by in vitro exposure to natalizumab. CONCLUSION: Natalizumab treatment increases the percentage of activated leukocytes producing proinflammatory cytokines in blood, presumably due to sequestration of activated cells in the peripheral circulation. GLOSSARY: AICD: = activation-induced cell death; IFN: = interferon; IL: = interleukin; mAb: = monoclonal antibody; MS: = multiple sclerosis; PBMC: = peripheral blood mononuclear cell; TGF: = transforming growth factor; TNF: = tumor necrosis factor.